2015
DOI: 10.1038/ncomms7091
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic origin of an ordered superstructure induced superconductivity in layered chalcogenides

Abstract: Interplay among various collective electronic states such as charge density wave and superconductivity is of tremendous significance in low-dimensional electron systems. However, the atomistic and physical nature of the electronic structures underlying the interplay of exotic states, which is critical to clarifying its effect on remarkable properties of the electron systems, remains elusive, limiting our understanding of the superconducting mechanism. Here, we show evidence that an ordering of selenium and sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 34 publications
4
50
2
Order By: Relevance
“…It is isostructural to CdI 2 (C6 structure)43 where sheets are stacked directly above each other. The same structure is found at ambient pressure in chemically similar systems with heavier atoms such as SnS 2 44 or SiTe 2 45 as well as in several other chalcogenides, iodides, chlorides and bromides4346474849, or even in BeH 2 50. The second lowest-enthalpy phase P 6 3 mc contains two layers per unit cell which are mutually staggered and reflected with respect to each other - Fig.…”
Section: Resultssupporting
confidence: 59%
“…It is isostructural to CdI 2 (C6 structure)43 where sheets are stacked directly above each other. The same structure is found at ambient pressure in chemically similar systems with heavier atoms such as SnS 2 44 or SiTe 2 45 as well as in several other chalcogenides, iodides, chlorides and bromides4346474849, or even in BeH 2 50. The second lowest-enthalpy phase P 6 3 mc contains two layers per unit cell which are mutually staggered and reflected with respect to each other - Fig.…”
Section: Resultssupporting
confidence: 59%
“…An ordered stacking of S/Ta/Se sandwiches is observed in 1T -TaSSe 33 . In the present work, we prepared a series of 1T -TaSe 2−x Te x (0 ≤ x ≤ 2) single crystals and obtained a phase diagram through the transport measurements.…”
mentioning
confidence: 92%
“…Previously, we found that the isovalent substitution in 1T -TaS 2−x Se x (0 ≤ x ≤ 2) system suppresses CCDW and NCCDW accompanied with superconductivity emergence in the middle doping area 14,15,33 . An ordered stacking of S/Ta/Se sandwiches is observed in 1T -TaSSe 33 .…”
mentioning
confidence: 99%
“…This question has been discussed in systems of reduced dimensionality which are prone to electronic instabilities, such as the coexistence of CDW order and superconductivity in 2H-NbSe 2 7 in contrast to the competition of CDW order and superconductivity in, for example, Yttrium cuprate 8 . The quasi-two dimensional layered transition-metal dichalcogenides (TMDs), many of which harbor CDW order, have served as model systems for the investigation of the interplay between CDWs and low T c superconductivity where low- T c superconductivity can be achieved by the application of pressure 9 to pristine 1T-TaS 2 or by partial substitution of Se for S 10 , Fe for Ta 11 or electric-field gate controlled intercalation of Li 12 and is always associated with the more conducting nearly commensurate CDW (NCCDW) phase and even the higher temperature incommensurate CDW (ICCDW) phase. Interestingly, in the pressure experiments on pristine 1T-TaS 2 , the low- T c superconductivity ( T c  ≈ 5 K) persists until the pressure is high enough to convert the CDW phase to a metal 9 .…”
Section: Introductionmentioning
confidence: 99%